EDUKASI KONSUMSI JUS STRAWBERRY DAN BUAH NAGA UNTUK MENINGKATKAN KADAR HEMOGLOBIN CALON PENDONOR DARAH - Putri, Tetra Anestasia; Suraduhita, Ayu; Aryani, Aryani; Milandari, Ratu; Delfiera, Firly Aulia; Zahra, Ardina Amelia (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
Prospective blood donors must meet standard requirements, namely for women. Based on the Minister of Health Regulation Number 91 of 2015, the normal hemoglobin level before blood donation is 12.5-17.0 gr/dL. The problem that often occurs is the frequent refusal of blood donors which is dominated by blood donor levels. Low hemoglobin (Hb). Oxidative stress is one of the conditions that affects Hb levels. Oxidative stress is one of the conditions that affects hemoglobin levels. Strawberries contain many phytochemicals, especially phenolic compounds which are beneficial for health. Red dragon fruit is a plant that can be used as a source of antioxidants. Mechanism of administering a combination of Straga juice as a fruit rich in antioxidants can change superoxide, hydroxyl and peroxyl lipid radicals to become less reactive. The aim of this activity is to increase Hb levels in prospective blood donors. Respondents in this community service were visitors to the AEON Mall Tanjung Barat shopping center on June 14 2024. The method of implementing this community service was giving juice and education. The results obtained from administering the Straga Juice Combination can increase the Hb levels of prospective voluntary blood donors by an average of 1.62 gr/dL. Based on the results of the questionnaire, on average, prospective donors have good knowledge about nutrition which can increase Hb levels, namely 80% (16 respondents) and 20% (4 respondents) have poor knowledge. Based on the results of community service activities that have been carried out. It can be concluded that the combination of Straga Juice can increase understanding and hemoglobin levels in prospective blood donors.